Lineage switch in relapse of acute leukemia with rearrangement of MLL gene (KMT2A). literature review and case reports - E. A. Zerkalenkova; O. I. Illarionova; A. N. Kazakova; N. I. Ponomareva; L. V. Baydun; E. Yu. Osipova; M. E. Dubrovina; A. M. Popov; T. V. Konyukhova; S. A. Plyasunova; N. V. Myakova; A. A. Maschan; et al. (Онкогематология, 2016)
Lineage switch is a rare phenomenon in which a transition from lymphoid to myeloid was observed in relapse of acute leukemia, or vice versa. This paper presents the four clinical case reports of acute lymphoblastic leukemia with MLL gene rearrangement (KMT2A) with myeloid phenotype in relapse.